Virtual Keroncong Music Performances As An Effort To Maintain Their Existence During The Covid-19 Pandemic (Jurnal Seni Musik, 2022)
The COVID-19 pandemic has had a negative impact on various sectors of the creative industry, especially in the performing arts. The prolonged impact of the COVID-19 pandemic has caused activities in the performing arts sector such as performing arts and music concerts which are usually held regularly to be unable to run. To maintain its existence, O. K Tjong Young Gita Citra Alam held a virtual keroncong music performance through social media platforms. The purpose of this study is to identify and describe the use of social media platforms in organizing virtual keroncong music performances as an effort to maintain the existence and media promotion of musical works. This study uses a qualitative method with a phenomenological approach. Data collection techniques were done through observation, interviews, and document studies. Triangulation was carried out to test the validity of the data obtained before being analyzed using the stages of data collection, data presentation, data reduction, and conclusions. The results show that O. K Tjong Young Gita Citra Alam uses social media platforms such as YouTube and Instagram as a medium to organize virtual music performances as a promotion and introduces works and maintains their existence. Social media platforms such as YouTube and Instagram are very effective, practical, and efficient promotional media because information uploaded through YouTube and Instagram accounts can be conveyed easily and can be reached and accessed quickly and easily by people around the world using smartphones, laptops, and computers connected to the internet.